Low-dose glucocorticoid improves progression-free survival of children with B cell acute lymphoblastic leukaemia following chimeric antigen receptor T-cell therapy - Zhang, Hui; Wang, Yuxuan; Ji, Qi; Zhang, Qinyi; Qiu, Chonglian; Huang, Saihu; Dong, Xingqiang; Pan, Jian; Lu, Jun; Bai, Zhenjiang; Hu, Shaoyan; Wu, Shuiyan (Frontiers in Immunology, 2025)
BackgroundThe prognostic impact of immunosuppressant therapies for cytokine release syndrome (CRS) and immune effector cell-associated neurotoxicity syndrome (ICANS), along with the outcomes and prognosis of children with relapsed/refractory B cell acute lymphoblastic leukaemia (B-ALL) undergoing chimeric antigen receptor (CAR) T-cell therapy, varies across populations. However, studies specifically focusing on these factors in the pediatric B-ALL population remain limited.MethodsWe investigated the effects of immunosuppressants on outcome efficacy and prognosis in a retrospective cohort of 120 patients treated with CAR T-cell infusion at a single institution from March 2017 to August 2023. The 30-day complete response rate, progression-free survival (PFS), overall survival (OS), and event-free survival (EFS) were evaluated.ResultsThe median age of the patients was 8.0 years (range, 2.2–18.0 years). Following CAR T-cell therapy, 91.67% of patients developed CRS and 25.83% developed ICANS. At 1 month after CAR T-cell infusion, 70.83% of patients received tocilizumab (TCZ), 24.17% received ruxolitinib (RUX), and 50.83% received glucocorticoids (GC) for CRS or ICANS management. By day 30, 92.08% of patients achieved a complete response. The complete-response rates did not differ between the GC and non-GC, TCZ and non-TCZ, or RUX and non-RUX groups. The median follow-up time was 20.6 months (range, 4.26–38.82 months). OS, EFS, and PFS did not significantly differ between the RUX and non-RUX or TCZ and non-TCZ groups. However, patients receiving low-dose GC (≤ 8 mg kg-¹) exhibited better PFS than the non-GC group, with multivariable analysis demonstrating low-dose GC as an independent protective factor for PFS (hazard ratio, 0.45; 95% confidence interval, 0.21–0.96).ConclusionsIn the context of CRS/ICANS management, low-dose GC independently confers long-term PFS benefits to pediatric B-ALL patients without compromising CAR T-cell activity when using appropriate GC, TCZ, or RUX regimens.